Corporate Ownership and Governance Reforms in Japan: Influence of Globalization and U.S. Practice - Hayashi, Mizuki (Columbia Journal of Asian Law, 2013)
This paper is a brief summary and discussion on the recent reforms of Japanese corporations in regards to ownership and board structure. The paper will examine the dissolving of traditional ownership models and legal reform of board structure through reviewing its influence such as recent shareholder activism, hostile takeover, the latest corporate scandal, and further reforms in the regulative environment of Japanese corporate governance in the past few years. Above all, the paper will delve into the conflicts and tensions created by the adoption of US-style shareholder activism or board structures in the corporate world among the Japanese business and legal practices in both country and firm level. The paper provides an analysis from both legal and social perspective, with a view of company as a decision-making group, and focuses on group cohesiveness of Japanese company derived from its ownership and employment structure. The analysis of recent ownership and board reform suggests that while ownership and board structure certainly converge toward Anglo-American style through the reform, the influence of the reforms on corporate governance is still limited or varies by firms, due to the high cohesiveness and conformity of Japanese companies derived from strong ties among their constituencies.